The Effects and Mechanisms of Lactate and Protons on the Human Umbilical Vein Endothelial (HUVEC) and Murine Melanoma (B16F10) Cells’ Migration, Adhesion, and Attachment. - Salem, Fatema Bajes (East Carolina University)
The tumor microenvironment is often acidic due to the high metabolic activity of cancer cells, causing the production of excess lactic acid. This elevated acidity significantly impacts the behavior of both normal and cancer cells, including cell migration, attachment, and cell spreading. Under acidic conditions, normal and cancer cells experience delayed migration, attachment, and spreading. In this study, by using cancer cells (B16F10) and endothelial cell (HUVEC) models, it was observed that increased acidity reduced the collective and directional migration compared to treatment at physiological pH, resulting in slower wound closure. A further reduction in collective and directional migration occurred under the combined effect of acidity and elevated lactate concentrations. Furthermore, increased lactate concentrations at the physiological pH (pH 7.4) resulted in a similar reduction in cell migration. Interestingly, increasing the acidity caused opposite cellular responses in both models used in this project regarding random motility. The elevated levels of acidosis caused a significant increase in the random motility of B16F10 cells, marked by the uncoordinated movements of the migrating cells, which is the opposite of what was observed in HUVECs, where acidosis reduced random motility. Moreover, the random motility decreased in both cell models under the combined effect of the elevated acidity levels and lactate concentrations relative to the treatment with acidity alone. Furthermore, B16F10 and HUVEC cells adapted a higher polarization and elongated cell morphology (shape) in an acidic microenvironment due to difficulty in tail detachment. The same phenomenon was observed in the cells treated with lactate at a physiological pH. However, in both cell models, the combined effect of acidity and lactate had an insignificant impact on cell length compared to acidic treatment only. Moreover, HUVECs formed multiple leading edges of "Lamellipodia" when exposed to an acidic buffer, while the melanoma cells did not exhibit this trait. Also, the percentage of HUVECs with multiple leading edges decreased under the combined influence of lactate and acidity, aligning closer to the levels seen with physiological pH. The interconnection between cell attachment, spreading, and cell migration was intensively studied. Cell attachment and spreading are the main primary stages in cell migration. They establish the initial contact and provide a correct mechanical force initiation and cellular signaling for the cell to migrate. In both cell models, the attachment and spreading delay was observed in acidic microenvironment, whereas the addition of lactate to the acidic treatment reversed these effects by reducing the negative impact of acidity in this assay. In this assay context, it was observed in both cell models that acidity blocked the transition of spreading cells to the polarized phase, and the combination effect of acidity and lactate reduced this transition blocking. Actin fibers play a crucial role in cell migration by providing structural support, enabling force generation, and coordinating signaling pathways. In both cell models, significantly high actin stress fibers were observed in an acidic microenvironment compared to physiological microenvironment. A similar situation was observed in HUVEC treated with high levels of lactate at physiological microenvironment, but not in B16F10 cells. The combined effect of lactate and acidity has an impact on reducing actin stress fibers in HUVECs, but this effect was not observed in the transformed cells. Changes in the location of focal adhesions and phosphorylation levels of focal adhesion kinase (FAK) and phosphorylated paxillin (pPAX) may significantly impact cell migration, attachment, and spreading. The acidic microenvironment caused alteration in the location and cluster size of phosphorylated pPAX (pPAX, Y118) and phosphorylated FAK (pFAK, Y397) during migration, attachment, and spreading in both cell models, displaying localization to the spreading cell periphery instead of the spreading cell body where dynamic focal adhesions are located compared to physiological pH-treated cells. Acidic treatment combined with lactate reduced the cluster size of pPAX (Y118) and pFAK (Y397) alongside alteration in their localization compared to acidic treatment without lactate. An additional measure was taken to evaluate the effects of acidic treatments on the phosphorylation levels of paxillin and focal adhesion kinase. The acidic microenvironment caused a decrease in FAK and PAX phosphorylation levels in both cell models and enhancement upon the addition of lactate to the acidic buffer in HUVEC but not the transformed cells.
Keywords: Lactate; Acidity; Normal cells; Cell attachment; Lactic acid; Endothelial cells; Cell adhesion; Cell migration; Cancer cells